Genotypic compatibility and spatial arrangements in spring sunflower and greengram (Phaseolus radiatus) intercropping - ALI, MASOOD; MISHRA, J P; SINGH, K K (The Indian Journal of Agricultural Sciences, 2013)
The field experiment was conducted duringÂ  spring/summer season of 1995 and 1996 on sandy loam soil at Research Farm of Indian Institute of Pulses Research, Kanpur.Three genotypes of greengram (Phaseolus radiatus L.),ie 'PDM 11','PDM 84-136' and 'PS 16' were intercroped with 'Morden' sunflower (Helianthus annuus L.) in 4:1, 6:1 and 6:2 row ratuo (greengram : sunflower). Highest seed yield of greengram genotypes as well as of sunflower was recorded in their respective sole stand which reduced considiserably with intercropping. The toal productivityÂ  of the system and land-use efficiency increased considerably under intercropping. the highest mean sunflower equivalent yield (1.726 kg/ha) and land equivalent ratio (1.19) was recorded from intercropping of 'PS 16' greengram with sunflower in 6.2 row ratio.